The Effect of Using Gadgets on Children Against Sundanese Cultural Values Silih Asah, Silih Asih and Silih Asuh - Leni Yulia; Zihan Suryani; Yona Wahyuningsih (CV. Rayyan Dwi Bharata, 2023)
The use of information and communication technology is increasing. Starting from elementary school age children to seniors. Gadget is a technology that many users. The impact of using technology such as gadgets, especially on children, will affect the cultural values attached to children. In the Sundanese environment, Sundanese cultural values become a distinctive identity, especially the cultural values of compassion and care. But it is undeniable, Sundanese cultural values are currently being affected due to the use of gadgets that are used starting from children. Many of the Sundanese values have decreased until they are no longer visible in the child's identity.